Relationship between Parental Stimulation and Development of Toddler Aged 1-3 Years - Pebrina, Melia; Putri, Amalia Riva; Fernando, Fenny; Fransisca, Dewi; Hayu, Ramah (Journal of Health Science and Medical Therapy, 2025)
The role of parents is one of the essential factors in child development. The stimulation that parents provide to children will create children who are smart, independent, have normal emotions and grow and develop optimally. The purpose of this study is to determine the relationship of stimulation to the development of toddlers aged 1-3 years in the Working Area of the Lubuk Begalung Health Center, Padang City. For this type of research, quantitative research with a cross-sectional study design and a retrospective approach was carried out in the Working Area of the Lubuk Begalung Health Center, Padang City. Data collection was carried out in November 2023. The sample from the study was 75 mothers who had toddlers aged 1-3 years. The techniques used are Consecutive Sampling, data collection using KPSP questionnaires, and stimulation. Univariate and bivariate data analysis using the Chi-Square test with a confidence degree of 95% (α = 0.05).